The cash conversion cycle and performances of consumer products in Malaysia - Nur shafiqah, binti Tukino (Universiti Malaysia Sarawak, (UNIMAS), 2012)
The purpose of this research is to explore the relationship between the firm's Cash Conversion Cycle with its profitability, size and cash flow. The collected data of this study was obtained from the DataStream ofthe consumer products listed on Bursa Malaysia for the period from 2006 to 2010. They were 119 finns - data collected after deleted non-applicable items. The researcher utilized Simple Linear Regression and Spearman's Correlation Analyses for empirical investigation on the hypotheses. These results in regression analysis provide a strong negative significant relatioQ.Ship between Cash Conversion Cycle and firm's size and firm's cash flow. Nevertheless, the relationship between Cash Conversion Cycle and firm's profitability showed no significant relationship between the two variables measured. Thus, this reveals that the increasing of independent variables (Net sales, Total assets, Cash & short tenn investment) results to lower Cash Conversion Cycle. Hence, in purpose to create shareholder value, the managing director sho~dd emphasize and concern on generating ultimate firm's siZe and firm's cash flow as to experience well perfonnance in Cash Conversion Cycle.